2022
DOI: 10.1101/2022.11.30.518494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intercellular Mitochondrial Transfer as a Rescue Mechanism in Response to Protein Import Failure

Abstract: Mitochondrial biogenesis requires the import of most of their proteins from the cytosol. Therefore, efficient import apparatus is vital for eukaryotic cell function, particularly in highly energy demanding cells such as neurons and myocytes. Consequently, dysfunctional mitochondrial protein import is implicated in many diseases. This study explores the molecular basis and consequences of import failure in mammalian cells. We show that blocking import machinery has profound effects on mitochondrial ultra-struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 68 publications
4
17
0
Order By: Relevance
“…This is consistent with previous reports that showed Tau P301L accumulation in the OMM and IMS (Cieri et al, 2018; Hu et al, 2016), and suggests that it may be associated with the translocation channel in a similar way to an artificially trapped precursor protein (Chacinska et al, 2003; Ford et al, 2022; Hope I Needs et al, 2022). Surprisingly, however, despite association of Tau P301L with the import machinery, in-cell NanoLuc import assays (Hope I. Needs et al, 2022) showed that the import kinetics of a precursor reporter were not significantly affected (Fig.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This is consistent with previous reports that showed Tau P301L accumulation in the OMM and IMS (Cieri et al, 2018; Hu et al, 2016), and suggests that it may be associated with the translocation channel in a similar way to an artificially trapped precursor protein (Chacinska et al, 2003; Ford et al, 2022; Hope I Needs et al, 2022). Surprisingly, however, despite association of Tau P301L with the import machinery, in-cell NanoLuc import assays (Hope I. Needs et al, 2022) showed that the import kinetics of a precursor reporter were not significantly affected (Fig.…”
Section: Resultssupporting
confidence: 93%
“…This can be achieved with the small molecule inhibitor MB20 (Cheung, 2017), or with a precursor fused to DHFR which, when bound to methotrexate, becomes trapped in the channel (Chacinska et al, 2003; Ford et al, 2022). While these treatments inhibit import in isolated mitochondria (Cheung, 2017; Ford et al, 2022), we unexpectedly found that they fail to do so within whole cells (Hope I Needs et al, 2022). We wondered if the apparent lack of effect on the whole mitochondrial population of the cell could be explained by a mitochondrial replacement system.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations